2002
DOI: 10.1042/ba20020066
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of meningococcal C oligosaccharide conjugate vaccines by size‐exclusion chromatography/multi‐angle laser light scattering

Abstract: The mean molecular masses of three different meningococcal C saccharide (MenC)-protein conjugate vaccines and their constituent proteins were estimated using HPLC size-exclusion chromatography (SEC) with multi-angle laser light scattering (MALLS) and refractive-index (RI) detection (SEC/MALLS). Chromatography of two CRM(197) conjugates (MenC-CRM(197)-A and MenC-CRM(197)-B) and one tetanus toxoid (TT) conjugate (MenC-TT) was performed in PBS, pH 7.4, on TSK-Gel (TosoHaas) analytical columns [CRM(197) is a non-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Measurement of the specific refractive indices (dn/dc) of the two conjugates gave similar values (0.235 ml/ g for T5-rEPA and 0.231 ml/ g for T8-rEPA) which were slightly higher than that of the carrier protein (0.206 ml/g). Previous work had also shown that the larger meningococcal group C conjugates also had dn/dc ratios higher than determined for individual PS or proteins, 24 and this result reaffirms the need to determine dn/dc for each sample.…”
Section: Safety Evaluation Of S Aureus Conjugate Vaccinesupporting
confidence: 56%
“…Measurement of the specific refractive indices (dn/dc) of the two conjugates gave similar values (0.235 ml/ g for T5-rEPA and 0.231 ml/ g for T8-rEPA) which were slightly higher than that of the carrier protein (0.206 ml/g). Previous work had also shown that the larger meningococcal group C conjugates also had dn/dc ratios higher than determined for individual PS or proteins, 24 and this result reaffirms the need to determine dn/dc for each sample.…”
Section: Safety Evaluation Of S Aureus Conjugate Vaccinesupporting
confidence: 56%
“…SEC-MALS/RI/viscosity of Vi polysaccharides in different eluents demonstrated the need to consider column choice and buffers salts to obtain representative recoveries and highlighted the differences that salt composition makes to hydrodynamic size and viscosity (Hitri et al 2019). See also the following examples of other vaccine-relevant oligo-and poly-saccharide components (Jumel et al 2002;Bardotti et al 2008;Harding et al 2012;Lockyer et al 2015).…”
Section: Molecular Size Profiling and Solution Properties Of Glycoconjugate Vaccinesmentioning
confidence: 99%
“…The resulting conjugate is primarily end-linked, but can also contain cross-linked molecules, albeit to a much lesser extent than conjugates made from randomly activated PS. d DP of OS around 20–47 102 , 103 . e De- O -acetylated OS; perhaps optional if within parentheses.…”
Section: Factors Determining the Glycan Chain Length Of Vaccine Preparationsmentioning
confidence: 99%